Extended spectrum beta-lactamases among hospitalized patients in surgery wards, Ilam, Iran. - Sadeghifard, Nourkhoda; Ghafourian, Sobhan; Sekawi, Zamberi; Neela, Vasantha Kumari; Hematian, Ali; Pakzad, Iraj; Galehdari, Elham Abouali; Mohebi, Reza (OMICS Publishing, 2011)
Objectives of this study were to study the molecular epidemiology of ESBL-producing Klebsiella pneumoniae in selective hospitals in Iran, to determine the prevalence of TEM, SHV and CTX-M genes responsible for ESBL production among ESBL-producing K. pneumoniae, to investigate the susceptibility of Klebsiellae spp producing ESBLs towards non-beta-lactam antibiotics, all in different seasons. Clinical isolates of K. pneumoniae were identified during Mar. 2007 to Apr. 2008 in Ilam hospitals, the province in west of Iran. All isolates were found in surgery wards. ESBL activity was first evaluated using the standard disc diffusion test for cephalosporins and monobactam, then using the double-disc synergy test between cephalosporins and clavulanate. PCR assay had done for ESBLs genes detection. The results showed sixteen K.pneumoniae were identified by chemical methods. No resistance had occurred among K.pneumoniae toward non-beta-lactam antibiotics. BlaSHV was dominant gene responsible for ESBLs production while just one blaTEM along with blaSHV were found. BlaCTX-M was not responsible for ESBLs production in our study. 37.5% K.pneumoniae producing ESBLs in surgery ward in west of Iran must be considerable and need to further study in different part of hospital in Ilam and in Iran. Strict antibiotic policy should be adopted in hospitals to estimate the impact of higher resistance in bacteria and to take steps for reducing these resistances.